(untitled) (Applied Biological Research, 2019)
A field experiment was conducted in a split-plot design at MRCFC, SKUAST-K, Khudwani (Kashmir) in kharif 2012 and 2013 to assess the effect of water regimes and weed management practices on water productivity. photosynthetically active radiation (PAR) interception, leaf SPAD values and rice yield under system of rice intensification. The treatments comprised of 3 irrigation regimes [alternate wetting and drying (AWD), saturation conditions and continuous flooding, and 7 weed manage ment practices, pyrazosulfuron ethyl @ 20 g a.i. ha-1 at 3 days after transplantation (DAT); cyhalofop butyl @ 80 g a.i, ha-1(15 DAT); pyrazosulfuron ethyl 20 g a.i. fb cyhalofop butyl 80 g a.i. ha-1(3 and 15 DAT); butachlor @ 1.5 kg a.i., ha-1(3 DAT); cono weeding, control and weed free condition. High PAR interception was noticed in flooding water regime at 30 DAT followed by saturation water regime. All test water regimes were at par in SPAD values. Water expense due to weed management practices was non-significant. Higher water expense efficiency, PAR and SPAD values were observed in sequential application of pyrazosulfuron-ethyl @ 20 g a.i., ha-1fb cyhalofop-butyl @ 80 g a.i., ha-1. Significantly higher grain yield was found in saturated water regime. A yield superiority of 3.6 and 5.9% was found by saturated water regime over AWD and continuous flooding. Amongst the herbicides, pyrazosulfuron-ethyl @ 20 g ha-1(3 DAT) fb cyhalofop-butyl @ 80 g ha-1(15 DAT) gave significantly higher grain yield over weedy check. The mean yield advantage by the use of pyrazosulfuron ethyl fb cyhalofop-butyl was 19.3, 14.0 and 10.3% over cyhalofop-butyl, cono-weeding and butachlor, respectively, during both the years.